Efficacy of Sofosbuvir/Ledipasvir in Adolescents With Chronic Hepatitis C Genotypes 1, 3, and 4: A Real-world Study. Issue 1 (January 2021) - Serranti, Daniele; Nebbia, Gabriella; Cananzi, Mara; Nicastro, Emanuele; Di Dato, Fabiola; Nuti, Federica; Garazzino, Silvia; Silvestro, Erika; Giacomet, Vania; Forlanini, Federica; Pinon, Michele; Calvo, Pier Luigi; et al.
ABSTRACT: Objectives: Sofosbuvir/Ledipasvir (SOF/LDV) has been approved by the European Medicine Agency (EMA) for the treatment of children and adolescents (at least 3 years of age) with chronic hepatitis C (CHC) genotype 1, 3, and 4 infection. The aim of this study was to evaluate the efficacy and safety of SOF/LDV in adolescents (12 to <18 years old) with CHC in the real-world setting. Methods: Prospective, open-label, multicentre study involving 12 Italian centres. Patients received the fixed-dose combination of SOF/LDV (400/90 mg) once daily ± ribavirin as per EMA approval and recommendations. The key efficacy endpoint was sustained virological response 12 weeks after the end of treatment (SVR12) as per intention-to-treat analysis. Safety was assessed by adverse events and clinical/laboratory data. Results: Seventy-eight consecutive adolescents (median age 15.2 years, range 12–17.9; girls 53.8%) were enrolled and treated between June 2018 and December 2019. Genotype distribution was as follows: genotype 1 (82.1%), 3 (2.5%), and 4 (15.4%). Seventy-six (97.4%) patients completed treatment and follow-up. Overall, SVR12 was 98.7%. One patient was lost to follow-up after 4 weeks of treatment; 1 patient completed treatment and missed the follow-up visit. No virological breakthrough or relapse were observed. No patient experienced grade 3 to 4 adverse event or serious adverse event. Conclusions: The results of this real-world study confirmed the high efficacy and the optimal safety profile of SOF/LDV for treatment of CHC in adolescents.